2023
DOI: 10.1186/s12985-023-02104-0
|View full text |Cite
|
Sign up to set email alerts
|

Potassium ion channels as a molecular target to reduce virus infection and mortality of honey bee colonies

Abstract: Declines in managed honey bee populations are multifactorial but closely associated with reduced virus immunocompetence and thus, mechanisms to enhance immune function are likely to reduce viral infection rates and increase colony viability. However, gaps in knowledge regarding physiological mechanisms or ‘druggable’ target sites to enhance bee immunocompetence has prevented therapeutics development to reduce virus infection. Our data bridge this knowledge gap by identifying ATP-sensitive inward rectifier pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…At the molecular level, this regulation is facilitated by inward rectifying potassium channels (Kir channels). Exposure of K ATP channels, a subtype of Kir channels that plays a fundamental role in the viral protection of honeybees 15 , to pharmacological activators induces an increase in immunocompetence and a reduction in mortality associated with viral infections in honeybees 20 . Conversely, several small molecules with insecticidal activity are being developed to target Kir channels and disrupt potassium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, this regulation is facilitated by inward rectifying potassium channels (Kir channels). Exposure of K ATP channels, a subtype of Kir channels that plays a fundamental role in the viral protection of honeybees 15 , to pharmacological activators induces an increase in immunocompetence and a reduction in mortality associated with viral infections in honeybees 20 . Conversely, several small molecules with insecticidal activity are being developed to target Kir channels and disrupt potassium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that activating the RNAi-system by feeding virus-specific dsRNA to larvae or adult bees before infection with DWV or Israeli Acute Paralysis Virus (IAPV) reduces the viral load, mortality, and symptoms resulting from the specific viral infection (Hunter et al, 2010; Desai et al, 2012). Potassium ion channel manipulation has also been proven effective treatment for IAPV (Fellows et al, 2023). Neither of these methods, however, are currently approved for use in the field, and there is no licensed specific treatment or prophylaxis for DWV (Smeele et al, 2023).…”
Section: Introductionmentioning
confidence: 99%